Economics of Rubber Production in Jhapa, Nepal - Poudel, Mousami; Adhikari, Prabin; Dhungana, Suryamani; Paudel, Shankar; Thapa, Kanti; Bidari, Angila; Manandhar, Ramita (Journal of Agriculture and Natural Resources, 2020)
A study was conducted to examine cost structure and economic feasibility of rubber production in Jhapa district. It also aimed to assess determinants of increment in acreage of rubber cultivation in the study area. A total of sixty two rubber growers were selected by simple random sampling and interviewed with pre-tested semi structured schedule on the month of March, 2019. Study revealed that the total cost of natural rubber production per hectare of rubber orchard was 499774.8 NRs. /year. It was found to be economically viable and cost effective as indicated by satisfactory values of Benefit Cost Ratio (1.5), Net Present Value of NRs. 686547 at a discount rate of 12 percent and Internal Rate of Return 18 percent. Probit model revealed that trainings received, experience of rubber farming, ethnicity and membership in community organizations were significant factors that positively affected farmers’ decision in expanding rubber cultivation area. Received trainings solely could increase probability of acreage increment by 36.9 percent. Thus, it is recommended that extension services like training, farmers’ field school, and farm visits should be intensified for increment of profitability from rubber farming in Jhapa, Nepal.